Towards a multi-scale understanding of the gas-star formation cycle in the Central Molecular Zone - Kruijssen, Diederik (Proceedings of the International Astronomical Union, 2016)
The Central Molecular Zone (CMZ, the central 500 pc of the Milky Way) contains the largest reservoir of high-density molecular gas in the Galaxy, but forms stars at a rate 10-100 times below commonly-used star formation relations. We discuss recent efforts in understanding how the nearest galactic nucleus forms its stars. The latest models of the gas inflow, star formation, and feedback duty cycle reproduce the main observable features of the CMZ, showing that star formation is episodic and that the CMZ currently resides at a star formation minimum. Using orbital modelling, we derive the three-dimensional geometry of the CMZ and show how the orbital dynamics and the star formation potential of the gas are closely coupled. We discuss how this coupling reveals the physics of star formation and feedback under the conditions seen in high-redshift galaxies, and promotes the formation of the densest stellar clusters in the Galaxy.
Gesehen am 29.05.2020
Published online by Cambridge University Press: 09 February 2017